No evidence of divergence at neutral genetic markers between the two morphologically different subspecies of the most numerous Arctic seabird. (20th August 2015) - Wojczulanis‐Jakubas, Katarzyna; Kilikowska, Adrianna; Fort, Jérôme; Gavrilo, Maria; Jakubas, Dariusz; Friesen, Vicki; Collinson, Martin
<x xml:space="preserve">Abstract</x> Identifying natural populations that might be considered separate units using morphology, genotype or both is important in understanding the process of speciation and for conservation. We examined the relationships between the only two subspecies of the most numerous Arctic seabird, the Little Auk Alle alle, using both morphological (wing and head‐bill lengths) and genetic data (482 base pairs of the mitochondrial control region and seven nuclear microsatellite loci). We found significant morphological differences between the subspecies, A. a. polaris being significantly larger than the nominate A. a. alle. However, we did not find the subspecies to be differentiated at either mitochondrial DNA or at microsatellite loci. Consequently, one evolutionary significant unit is proposed. The similarity of the two subspecies at neutral genetic markers may be due to contemporary gene flow between populations, as well as large population sizes both in the present and in the past, combined with recent post‐glacial colonization of the Artic.